2009
DOI: 10.1590/s1806-37132009001200004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência da doença do refluxo gastroesofágico em pacientes com fibrose pulmonar idiopática

Abstract: Objective: To determine the prevalence of gastroesophageal reflux disease (GERD) and to evaluate its clinical presentation, as well as the esophageal function profile in patients with idiopathic pulmonary fibrosis (IPF). Methods: In this prospective study, 28 consecutive patients with IPF underwent stationary esophageal manometry, 24-h esophageal pH-metry and pulmonary function tests. All patients also completed a symptom and quality of life in GERD questionnaire. Results: In the study sample, the prevalence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 22 publications
(33 reference statements)
0
14
0
5
Order By: Relevance
“…It has been assumed that the presumed benefit of PPIs in measures of lung function in IPF is due to a reduction in gastric acidity that would reduce potential lung injury due to microaspiration. Although GER commonly accompanies IPF [ 10 , 76 , 85 ]; and it is believed that anti-reflux strategies may benefit IPF [ 70 ], several reports have indicated the lack of direct and complete association between the progression of GER and IPF [ 10 , 77 , 80 , 86 88 ]. Paradoxically, some IPF patients who undergo fundoplication therapy have been initially placed on PPIs and failed to suppress symptoms of reflux such as heartburn and regurgitation despite the PPIs; making them eligible for the surgical procedure (see the question and answer section of ref [ 70 ]).…”
Section: Discussionmentioning
confidence: 99%
“…It has been assumed that the presumed benefit of PPIs in measures of lung function in IPF is due to a reduction in gastric acidity that would reduce potential lung injury due to microaspiration. Although GER commonly accompanies IPF [ 10 , 76 , 85 ]; and it is believed that anti-reflux strategies may benefit IPF [ 70 ], several reports have indicated the lack of direct and complete association between the progression of GER and IPF [ 10 , 77 , 80 , 86 88 ]. Paradoxically, some IPF patients who undergo fundoplication therapy have been initially placed on PPIs and failed to suppress symptoms of reflux such as heartburn and regurgitation despite the PPIs; making them eligible for the surgical procedure (see the question and answer section of ref [ 70 ]).…”
Section: Discussionmentioning
confidence: 99%
“…However, these findings have been controversial, because other groups have found no such difference in the rates of gastroesophageal pathologic features. Bandeira et al [40], in their prospective study of 28 patients with IPF, showed no significant differences with controls regarding the demographic characteristics, pulmonary function, clinical presentation, or manometric findings. Our study was in agreement with these findings with regard to showing no differences in the manometric, barium swallow, or gastric emptying study findings in patients with IPF compared with those with other etiologies of ESLD.…”
Section: Discussionmentioning
confidence: 99%
“…The association between nutritional status measurements and pulmonary function in children and adolescents with cystic fibrosis was analyzed by Chavez et al49 Bandeira et al demonstrated the prevalence of gastroesophageal reflux disease in patients with idiopathic pulmonary fibrosis 50. Costa et al described the role of inflammatory cells and their mediators in COPD pathogenesis 51.…”
Section: Methodsmentioning
confidence: 99%